Hole Application of Urea Inhibited Nitrification in the Zone around the Fertilizer Point by Reducing the Abundance of Nitrification Genes - Cheng, Liang; Wang, Yifan; Wang, Yiliu; Wang, Huoyan (Agriculture (Basel), 2022)
The present study investigated the interactions among nitrogen transformation and soil bacteria along the direction of diffusion of hole-applied urea. To this end, a lab incubation trial was conducted on sandy loam and silty loam soils. Soil bacterial communities were analyzed via 16S rRNA high-throughput sequencing, and soil chemical properties were measured at 8, 20, and 60 d after urea application. The treatments were the fertilizer point and 0–4 cm, 4–8 cm, 8–12 cm, and 12–16 cm horizontally distant from the fertilization point. They were designated FP, 0–4, 4–8, 8–12, and 12–16, respectively. The pre-culture and pre-incubation soil sample was used as a control. Soil NH4+ concentration was the key factor influencing the soil bacterial community. For the sandy loam, the FP and 0–4 treatments reduced the putative abundance of amoA by 38.9–83.4% and 40.7–67.6%, amoB by 38.9–83.4% and 40.6–67.6%, and amoC by 41.1–84.1% and 43.6–69.9%, respectively, compared with the control group. For the silty loam, the FP and 0–4 treatments reduced the putative abundance of amoA by 85.0–87.3% and 28.9–82.6%, amoB by 84.6–87.2% and 29.1–82.5%, and amoC by 81.9–87.1% and 27.5–82.7%, respectively, compared with the control group. The fertilizer core region was <4 cm from the fertilizer point and maintained high NH4+ concentrations for >60 d, which strongly inhibited nitrification. Overall, the fertilizer core region slowly released nitrogen and inhibited nitrification. For these reasons, hole application of urea may serve as a long-acting nitrogen fertilizer.